Gratification Delics: Assessing the Existence of Legal & Moral Norms - Rusdan, Muhammad; Arifai, Arifai; Rahim, Abdul Jabar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This paper aims to examine the offense of gratification when viewed from normal morals and legal norms. The results of the study show that in essence, the gratification offense is not only contrary to Article 12B of the anti-corruption law as a legal norm, but also violates moral norms. The natural law school believes that the offense of gratification is a violation of moral norms such as the value of justice, while the positivism school considers it a violation of legal norms. Ethically, the offense of gratification is an act that is inappropriate and contrary to public morality. The perpetrators of gratification offenses are driven by the nature of hedonism which only seeks outward pleasure without adhering to moral values that such actions can harm the wider community.